2020
DOI: 10.1108/ijcma-05-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

Deviance due to fear of victimization: “emotional intelligence” a game-changer

Abstract: Purpose With a foundation in the conservation of resource theory, this paper aims to examine the validity of a conceptual model that explains the mechanism connecting perceived threat of terrorism to production deviance. The link between perceived threat of terrorism and production deviance was examined via emotional exhaustion. Notably, the study evaluated whether the relationship between perceived threat of terrorism and production deviance is mediated by emotional exhaustion and moderated by levels of emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Furthermore, our results indicated that emotional intelligence negatively moderated the relationship between interpersonal conflict and CWB directed toward the organization and individuals (CWB-O and CWB-I) ( H2a and H2b supported) likely owing to employees high on emotional intelligence having less extreme emotional reactions to stressful events, such as interpersonal conflict, to help them cope with the event (Wong and Law, 2002). In the previous research, researchers also found a negative moderating role of emotional intelligence on the relationships between indirect supervisor conflict and employee deviant behavior (Ma and Liu, 2019), perceived threat of terrorism and workplace deviance (Shah et al , 2020), job pressures and auditors’ judgment (Yang et al , 2019), perceived stress and suicidal ideation (Abdollahi et al , 2016) and job insecurity and emotional and behavioral reactions (Jordan et al , 2002), indicating the crucial role of emotional intelligence in controlling emotional reaction to stressful events which may lead to negative consequences.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, our results indicated that emotional intelligence negatively moderated the relationship between interpersonal conflict and CWB directed toward the organization and individuals (CWB-O and CWB-I) ( H2a and H2b supported) likely owing to employees high on emotional intelligence having less extreme emotional reactions to stressful events, such as interpersonal conflict, to help them cope with the event (Wong and Law, 2002). In the previous research, researchers also found a negative moderating role of emotional intelligence on the relationships between indirect supervisor conflict and employee deviant behavior (Ma and Liu, 2019), perceived threat of terrorism and workplace deviance (Shah et al , 2020), job pressures and auditors’ judgment (Yang et al , 2019), perceived stress and suicidal ideation (Abdollahi et al , 2016) and job insecurity and emotional and behavioral reactions (Jordan et al , 2002), indicating the crucial role of emotional intelligence in controlling emotional reaction to stressful events which may lead to negative consequences.…”
Section: Discussionmentioning
confidence: 89%
“…Emotional intelligence also refers to a set of emotional abilities to understand, manage and use emotional information (Salovey and Mayer, 1990). Previous research has examined the moderating role of emotional intelligence on the relationships between different variables such as perceived stress and suicidal ideation (Abdollahi et al , 2016), personality and creativity (Jafri, 2020) and perceived threat of terrorism and workplace deviance (Shah et al , 2020). Results of previous studies suggest that emotional intelligence may also serve as a moderator on the relationship between interpersonal conflict and CWB.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In addition, a future bibliometric study could focus on the theories and methods that appear in the studies on this topic, thereby expanding this study's work. Finally, further bibliometric studies should capture the critical studies that were under development (Shah et al, 2020a;Shah et al, 2020b) whilst this paper was being developed.…”
Section: Ijcma 325mentioning
confidence: 99%
“…The literature discusses the impact and relationship of terrorism to economic and business activity Dau et al, 2018;Tingbani et al, 2019), its effect on trade and supply chain disruption (Argomaniz and Lehr, 2016;Branzei and Abdelnour, 2010; and its influence on employees' well-being and behaviours (Raja et al, 2020;Shah et al, 2018a;Shah et al, 2018b;Shah et al, 2020a;Shah et al, 2020b). Additionally, the economic repercussions of terrorism's indirect psychological effects can adversely impact productivity and consumer confidence Branzei and Abdelnour, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Constantly dealing with such conflicting demands may deplete frontline caregivers mentally as well as physically, that ultimately leads to emotional exhaustion. Research indicates that situations that call attention to concerns related to life threat contribute to psychological resource loss (Shah et al, 2020;Malik et al, 2018). Other literature has argued that health-care personnel who work on the frontline during pandemics are especially susceptible to mental and physical energy drainage (Lam et al, 2020;Shiao et al, 2007).…”
Section: Exhausting Job Demand To Satisfymentioning
confidence: 99%